Preparation method and application of a needle-shaped fluffy lead iodide composite nucleation interface
The electron transport layer is modified by lactic acid protonated imidazole salt to induce growth of needle-like three-dimensional fluffy lead iodide composite nucleation interface, which solves the problem of insufficient crystallinity and stability of perovskite films in the air environment, and achieves the preparation and stability improvement of high-quality perovskite films.
Patent Information
- Application Number
- CN202411793698.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The prior art When preparing perovskite films in an air environment, the crystallinity and poor environmental stability are poor, limiting the industrial application of perovskite films and their devices.
The electron transport layer was modified with the protonated imidazole salt of lactate as the nucleation template to induce the growth of a needle-like three-dimensional fluffy lead iodide composite nucleation interface, and a perovskite film was prepared by a two-step method.
It improves the crystal quality and environmental stability of perovskite films, and can prepare high-quality perovskite films in the air, which are suitable for harsh environments such as high humidity and high temperature.
Smart Images

Figure CN119263649B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of semiconductor device technology, and in particular to a two-step preparation method and application of a perovskite nucleation interface using a protonated lactic acid imidazolium salt-modified electron transport layer as a nucleation template to induce the growth of needle-shaped three-dimensional fluffy lead iodide. Background Art
[0002] In today's global environmental development situation, energy crisis and environmental pollution have become major challenges that need to be solved urgently, which has prompted the development of renewable green energy to become a major issue in energy utilization and environmental protection. In this process, materials that can use the photoelectric effect to convert abundant, clean and pollution-free solar energy into electrical energy have attracted much attention. Among them, halide perovskite materials have emerged as a semiconductor material with a wide range of optoelectronic application potential. Especially in the application of perovskite solar cells, high-quality perovskite films show highly crystalline characteristics due to the full reaction of their precursor components, the orderly growth of crystal orientation, and the full conversion and stable formation of α-phase perovskite crystals, which helps to improve the transmission efficiency of electrons and holes, reduce energy loss, and thus prolong the life of carriers, which directly affects the photoelectric conversion efficiency of perovskite solar devices. In addition, high-quality perovskite films also have excellent structural stability and can maintain excellent performance under a wider range of humidity and temperature conditions.
[0003] At present, the two-step deposition preparation technology of perovskite is one of the important ways to obtain high-quality perovskite films. Its advantage is that the growth and crystallization of perovskite can be effectively regulated by separating the deposition of lead iodide and organic mixed solution. However, this preparation method still faces some problems, such as incomplete conversion of lead iodide due to insufficient solid-liquid reaction, and the stringent requirements of the second step of organic amine salt deposition on the relative humidity of the environment. In response to the above problems, current research focuses on strategies such as precursor additive engineering, solvent engineering, and component engineering to optimize the two-step deposition process of perovskite to obtain high-quality and high-performance perovskite films. However, it is worth noting that the research on the first step of lead iodide deposition involving interface engineering to regulate the spatial structure of lead iodide is still relatively scarce, and the above strategy has not been able to completely get rid of the strict requirements on environmental humidity and temperature, which greatly limits the industrialization and wide application of perovskite films and their devices.
[0004] In view of this situation, it is a challenge to prepare high-quality perovskite solar films through a two-step method in the air. We are in urgent need of exploring better solutions to break through the current technical bottleneck and further promote the development of perovskite film preparation technology in depth, so as to meet the urgent needs of the energy field for efficient and stable solar cells and provide strong support for the optimization and improvement of the global energy supply system. Summary of the invention
[0005] In view of this, the purpose of the present application is to provide a method for preparing a needle-shaped fluffy lead iodide composite nucleation interface and its application, so as to solve the problems of poor crystallinity and poor environmental stability faced by the two-step method in the prior art when preparing perovskite films in an air environment.
[0006] In order to achieve the above technical objectives, the present application provides a method for preparing a needle-shaped fluffy lead iodide composite nucleation interface, comprising the following steps:
[0007] Step S1, preparing a lactic acid protonated imidazole salt solution: mixing lactic acid, 1-aminoethyl-3-methylimidazolium tetrafluoroborate, and water, and stirring evenly to obtain a lactic acid protonated imidazole salt solution;
[0008] Step S2, preparing a lactic acid protonated imidazolate interface modification layer: dripping a lactic acid protonated imidazolate solution on the surface of the SnO2 electron transport layer, obtaining a wet film containing lactic acid protonated imidazolate by spin coating, and annealing the wet film containing lactic acid protonated imidazolate to obtain a lactic acid protonated imidazolate interface modification layer;
[0009] Step S3, preparing a needle-shaped fluffy lead iodide composite nucleation interface: adding a lead iodide solution dropwise onto the surface of the lactic acid protonated imidazolium salt interface modification layer, obtaining a wet film containing lead iodide by spin coating, and annealing the wet film containing lead iodide to obtain a needle-shaped fluffy lead iodide composite nucleation interface.
[0010] Furthermore, the molar ratio of lactic acid to 1-aminoethyl-3-methylimidazolium tetrafluoroborate is 1:1; and the concentration of the protonated imidazole salt solution of lactic acid is 0.30-0.90 mg / mL.
[0011] Furthermore, in step S2, the annealing temperature is 80-120° C., and the annealing time is 5-10 minutes.
[0012] Furthermore, in step S3, the lead iodide solution is prepared by mixing lead iodide with an organic solvent.
[0013] Furthermore, the organic solvent is one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0014] Furthermore, the organic solvent consists of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 9:1.
[0015] Furthermore, in step S3, the annealing temperature is 60-80° C., and the annealing time is 0.5-2 minutes.
[0016] The present application provides a perovskite film with a needle-shaped fluffy lead iodide composite nucleation interface as a crystal framework, which is obtained by dynamically spin-coating an organic mixed solution on the needle-shaped fluffy lead iodide composite nucleation interface and then annealing.
[0017] The present application provides an application of a method for preparing a needle-shaped fluffy lead iodide composite nucleation interface, which is used for preparing a perovskite film in air or a high humidity environment.
[0018] The present application also provides a perovskite solar cell, comprising a conductive glass substrate, a SnO2 electron transport layer, a lactic acid protonated imidazole salt interface modification layer, a perovskite film with a needle-shaped fluffy lead iodide composite nucleation interface as a crystallization framework, a hole transport layer and a metal electrode layer, which are arranged in sequence.
[0019] In summary, the present application provides a method for preparing a needle-shaped fluffy lead iodide composite nucleation interface, wherein a synthesized lactic acid protonated imidazole salt solution is spin-coated on a SnO2 electron transport layer and annealed to obtain a nucleation induction template-lactic acid protonated imidazole salt interface modification layer; then a lead iodide solution is spin-coated on its surface, and annealed to obtain a needle-shaped three-dimensional fluffy lead iodide composite nucleation interface. The present application innovatively prepares a two-step perovskite nucleation interface using a lactic acid protonated imidazole salt modified electron transport layer as a nucleation template to induce the growth of needle-shaped three-dimensional fluffy lead iodide. This method can be used to prepare high-quality perovskite films in an air environment. Compared with the prior art, the present application scheme protonates the amino group on the imidazole salt by reacting lactic acid with the imidazole salt to obtain a lactic acid protonated imidazole salt, which is then spin-coated and annealed as an interface modification layer between the SnO2 electron transport layer and the perovskite film. The imidazole ring is affected by the electron cloud of lead iodide and polymerizes along the lead iodide to form a one-dimensional structure; at the same time, the imidazole ring also provides nucleation sites for lead iodide, which enables it to shuttle in the network formed by imidazole salts and be induced to generate one-dimensional needle-shaped compounds, thereby constructing a three-dimensional fluffy lead iodide composite nucleation interface, which has a positive role in optimizing the crystallinity and stability of perovskite films prepared by the two-step method: on the one hand, the special needle-shaped fluffy porous structure can effectively improve the wettability of the organic mixed solution in the second step, promote the full reaction with lead iodide, and greatly improve the crystallization quality of the perovskite film; on the other hand, its strong hydrophobicity can serve as an efficient barrier medium to effectively block the invasion of moisture in the air during the preparation of high-quality perovskite films, and greatly improve the environmental stability of the perovskite film in applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0021] Figure 1 The molecular reaction formula for preparing the protonated imidazole salt solution of lactic acid provided in Examples 1 to 3 of the present invention;
[0022] Figure 2 Field emission scanning electron microscope photos of the lead iodide nucleation interface provided in Examples 1 to 3 of the present invention and Comparative Example 1;
[0023] Figure 3 Field emission scanning electron microscope photographs of the lead iodide nucleation interface provided in Comparative Examples 2 and 3 of the present invention;
[0024] Figure 4 Quasi-in-situ X-ray diffraction patterns of the perovskite film annealing process provided in Example 3 of the present invention and Comparative Example 1;
[0025] Figure 5 X-ray diffraction patterns of the perovskite films provided in Example 3 of the present invention and Comparative Example 1;
[0026] Figure 6 Photoluminescence spectra of the perovskite films provided in Examples 1 to 3 of the present invention and Comparative Example 1;
[0027] Figure 7 Field emission scanning electron microscope photos of the perovskite thin film provided in Example 3 of the present invention and Comparative Example 1;
[0028] Figure 8 Atomic force microscope images of the perovskite films provided in Example 3 of the present invention and Comparative Example 1;
[0029] Fig. 9 Field emission scanning electron microscope photographs and X-ray diffraction patterns of the crystal degradation of the perovskite film provided in Example 3 of the present invention and Comparative Example 1 after being stored in a 70±10% humidity environment for 600 hours;
[0030] Fig.10 Field emission scanning electron microscope photos and X-ray diffraction patterns of the crystal degradation of the perovskite film provided in Example 3 of the present invention and Comparative Example 1 after being heated at 85° C. for 900 hours;
[0031] Fig.11 The photoelectric efficiency test diagram of the perovskite solar cell provided by Example 4 of the present invention and Comparative Examples 4 to 6;
[0032] The abbreviations shown in the figure are interpreted as follows:
[0033] Contorl: Lead iodide nucleation interface / perovskite film / perovskite solar cell provided in the embodiment without using lactic acid protonated imidazolium salt buried modification;
[0034] LA-Mlm: lead iodide nucleation interface / perovskite film / perovskite solar cell modified by protonated imidazolium salt of lactic acid provided in the embodiment;
[0035] LA / PbI2: lead iodide nucleation interface modified by lactic acid burying provided in the embodiment;
[0036] Mlm / PbI2: Lead iodide nucleation interface modified by burying with 1-aminoethyl-3-methylimidazolium tetrafluoroborate as provided in the example. DETAILED DESCRIPTION
[0037] The technical solutions of the embodiments of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the specification of the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection requested by the present application.
[0038] The sources of all raw materials in the present invention are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0039] The present invention provides a method for preparing a needle-shaped fluffy lead iodide composite nucleation interface, comprising the following steps:
[0040] Step S1, preparing a lactic acid protonated imidazole salt solution: mixing lactic acid, 1-aminoethyl-3-methylimidazolium tetrafluoroborate, and water, and stirring evenly to obtain a lactic acid protonated imidazole salt solution;
[0041] Step S2, preparing a lactic acid protonated imidazolate interface modification layer: dripping a lactic acid protonated imidazolate solution on the surface of the SnO2 electron transport layer, obtaining a wet film containing lactic acid protonated imidazolate by spin coating, and annealing the wet film containing lactic acid protonated imidazolate to obtain a lactic acid protonated imidazolate interface modification layer;
[0042] Step S3, preparing a needle-shaped fluffy lead iodide composite nucleation interface: adding a lead iodide solution dropwise onto the surface of the lactic acid protonated imidazolium salt interface modification layer, obtaining a wet film containing lead iodide by spin coating, and annealing the wet film containing lead iodide to obtain a needle-shaped fluffy lead iodide composite nucleation interface.
[0043] Specifically, in step S1, when preparing the lactic acid protonated imidazole salt solution, stirring can be performed at room temperature or at a temperature of 40 to 70° C., and the stirring time is 0.5 to 12 hours.
[0044] Specifically, a SnO2 solution is dripped onto the surface of a conductive glass substrate, a wet film containing SnO2 is obtained by spin coating, and the wet film containing SnO2 is annealed to obtain a SnO2 electron transport layer.
[0045] It should be noted that in step S3, the imidazole ring in the protonated imidazole salt of lactic acid reacts with lead iodide to generate one-dimensional needle-shaped compound crystals, which are stacked and staggered to form a lead iodide composite nucleation interface with three-dimensional fluffy and porous characteristics. This structure has multiple advantages: on the one hand, its needle-shaped, fluffy and porous interface can enhance the wettability of the organic mixed solution in the subsequent coating process, so that the organic mixed solution diffuses and fully reacts in the lead iodide layer, which is conducive to the formation of a perovskite film with large grains and uniform distribution and high crystalline quality; on the other hand, due to the hydrophobic properties of the imidazole ring, the three-dimensional network formed can build a protective barrier for the interface, which can effectively resist the intrusion of moisture, so that high-quality perovskite films can be prepared in the air. Therefore, under harsh environmental conditions such as high humidity and high temperature, the perovskite film can show excellent stability, effectively inhibit the occurrence of decomposition, and provide a strong guarantee for the application of perovskite solar cells in complex environments.
[0046] In some embodiments, the molar ratio of lactic acid to 1-aminoethyl-3-methylimidazolium tetrafluoroborate is 1:1; and the concentration of the protonated imidazole salt solution of lactic acid is 0.30-0.90 mg / mL.
[0047] In some embodiments, in step S2, the annealing temperature is 80-120° C., and the annealing time is 5-10 minutes.
[0048] In some embodiments, in step S3, the lead iodide solution is prepared by mixing lead iodide with an organic solvent.
[0049] Specifically, the molar concentration of lead iodide in the organic solvent is 1.35-1.55 M.
[0050] Preferably, the organic solvent is one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0051] More preferably, the organic solvent consists of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 9:1.
[0052] Preferably, in step S3, the annealing temperature is 60-80° C., and the annealing time is 0.5-2 minutes.
[0053] The embodiment of the present invention provides a perovskite film with a needle-shaped fluffy lead iodide composite nucleation interface as a crystal framework, which is obtained by dynamically spin-coating an organic mixed solution on the needle-shaped fluffy lead iodide composite nucleation interface and then annealing.
[0054] Preferably, the organic mixed solution is prepared by uniformly mixing formamidine iodide, methylammonium chloride and a second organic solvent.
[0055] Specifically, the mass ratio of formamidine iodide to methylammonium chloride is 90: (10-18); the second organic solvent is one of isopropanol and anhydrous ethanol; the annealing temperature is 150-180° C., and the annealing time is 10-20 minutes.
[0056] The embodiment of the present invention also provides an application of a method for preparing a needle-shaped fluffy lead iodide composite nucleation interface, which is used for preparing a perovskite film in air or in a high humidity environment.
[0057] Specifically, it is applied in a high humidity environment with a humidity of 40±10%.
[0058] An embodiment of the present invention also provides a perovskite solar cell, comprising a conductive glass substrate, a SnO2 electron transport layer, a lactic acid protonated imidazolium salt interface modification layer, a perovskite film with a needle-shaped fluffy lead iodide composite nucleation interface as a crystallization framework, a hole transport layer, and a metal electrode layer, which are arranged in sequence.
[0059] The applicant further provides the following reference specific embodiments to describe the present invention. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0060] Example 1
[0061] This embodiment provides a method for preparing a needle-shaped fluffy lead iodide composite nucleation interface, and a perovskite film with the needle-shaped fluffy lead iodide composite nucleation interface as a crystal framework, which is obtained by dynamically spin-coating an organic mixed solution on the needle-shaped fluffy lead iodide composite nucleation interface and then annealing. The specific steps are as follows:
[0062] Step S1, solution preparation:
[0063] Lactic acid protonated imidazolate solution: Mix 0.63 mg lactic acid, 0.27 mg 1-aminoethyl-3-methylimidazolate tetrafluoroborate, and 3 mL deionized water, and stir evenly to obtain a lactic acid protonated imidazolate solution with a concentration of 0.30 mg / mL; the molecular formula of the preparation process of the lactic acid protonated imidazolate solution can be found in Figure 1 .
[0064] Lead iodide solution: 691.52 mg of lead iodide was dissolved in 1 mL of a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide to obtain a lead iodide solution after sufficient dissolution; wherein the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide in the mixed solution is 9:1;
[0065] Organic mixed solution: Mix 90 mg of formamidine iodide, 14 mg of methylammonium chloride and 1 mL of isopropanol solvent and fully dissolve to obtain an organic mixed solution;
[0066] Step S2, taking the FTO glass substrate and washing it with deionized water, acetone, ethanol and isopropanol for 20 minutes in sequence, then blowing it dry with nitrogen gas, and irradiating it with ultraviolet light for 30 minutes;
[0067] Step S3, dropping 50 μL of a SnO2 solution with a mass concentration of 2.67% on the surface of the conductive glass substrate, obtaining a wet film containing SnO2 by spin coating, and annealing the wet film containing SnO2 at 150° C. for 30 minutes to obtain a SnO2 electron transport layer;
[0068] Step S4, dropping 50 μL of lactic acid protonated imidazolate solution on the surface of the SnO2 electron transport layer, obtaining a wet film containing lactic acid protonated imidazolate by spin coating, and annealing the wet film containing lactic acid protonated imidazolate at 150° C. for 30 minutes to obtain a lactic acid protonated imidazolate interface modification layer;
[0069] Step S5, adding 50 μL of lead iodide solution to the surface of the protonated imidazole salt interface modification layer of lactic acid, obtaining a wet film containing lead iodide by spin coating, and annealing the wet film containing lead iodide at 70° C. for 1 minute to obtain a needle-shaped fluffy lead iodide composite nucleation interface;
[0070] Step S6, adding 50 μL of an organic mixed solution onto the surface of the needle-shaped fluffy lead iodide composite nucleation interface, obtaining a wet film containing organic salts by dynamic spin coating, and annealing the wet film containing organic salts at 150° C. for 15 minutes to obtain a perovskite film with the needle-shaped fluffy lead iodide composite nucleation interface as a crystal framework.
[0071] Example 2
[0072] The difference from Example 1 is that the concentration of the protonated imidazole salt solution of lactic acid is different. The specific preparation method is as follows: 0.63 mg of lactic acid, 0.27 mg of 1-aminoethyl-3-methylimidazolium tetrafluoroborate, and 1 mL of deionized water are mixed and stirred evenly to obtain a protonated imidazole salt solution of lactic acid with a concentration of 0.90 mg / mL.
[0073] Example 3
[0074] The difference from Example 1 is that the concentration of the protonated imidazole salt solution of lactic acid is different. The specific preparation method is as follows: 0.63 mg of lactic acid, 0.27 mg of 1-aminoethyl-3-methylimidazolium tetrafluoroborate, and 1.5 mL of deionized water are mixed and stirred evenly to obtain a protonated imidazole salt solution of lactic acid with a concentration of 0.60 mg / mL.
[0075] Comparative Example 1
[0076] The difference from Example 3 is that no lactic acid protonated imidazole salt solution is used to perform bottom modification on the SnO2 electron transport layer.
[0077] Comparative Example 2
[0078] The difference from Example 3 is that lactic acid solution is used instead of lactic acid protonated imidazole salt solution.
[0079] Comparative Example 3
[0080] The difference from Example 3 is that 1-aminoethyl-3-methylimidazolium tetrafluoroborate solution is used instead of the lactic acid protonated imidazole salt solution.
[0081] The lead iodide nucleation interface prepared in step S5 of the above Examples 1 to 3 and Comparative Examples 1 to 3 was characterized:
[0082] Characterization 1, field emission scanning electron microscopy analysis, test results see Figure 2 and Figure 3 :
[0083] The lead iodide nucleation interface prepared in step S5 of Examples 1 to 3 and Comparative Examples 1 to 3 was scanned and analyzed using field emission scanning technology. The corresponding electron microscope images are shown in FIG. Figure 2 and Figure 3 As shown. Figure 2 From the parts b to d, it can be seen that the lead iodide layer modified by protonated imidazolate with lactic acid has a one-dimensional needle-like compound generated on the surface, while the one-dimensional needle-like compound is not observed in the comparative example 1 without protonated imidazolate with lactic acid. Figure 3 It can be seen that when the protonated imidazolium salt of lactic acid is replaced by lactic acid or 1-aminoethyl-3-methylimidazolium tetrafluoroborate of the same molar concentration to bury and modify the lead iodide layer, no one-dimensional needle-shaped compound is observed in Comparative Example 2 using lactic acid burying modification; some needle-shaped and columnar mixed lead iodide was observed in Comparative Example 3 using 1-aminoethyl-3-methylimidazolium tetrafluoroborate to bury and modify, indicating that its crystal nucleation is insufficient and its orientation is not completely controlled. This shows that only when the lead iodide layer is buried and modified with protonated imidazolium salt of lactic acid, a needle-shaped three-dimensional fluffy lead iodide composite nucleation interface can be formed.
[0084] Specifically, when the lead iodide layer was modified with a protonated lactic acid imidazolate solution at a concentration of 0.30 mg / mL, only a small amount of one-dimensional needle-like compounds were generated on the surface of the lead iodide layer. As the concentration of the protonated lactic acid imidazolate solution gradually increased, the amount of one-dimensional needle-like compounds generated on the surface of the lead iodide layer showed a trend of continuous increase. When the concentration of the protonated lactic acid imidazolate solution increased to 0.60 mg / mL and 0.90 mg / mL, the lead iodide layer was transformed into a three-dimensional fluffy porous lead iodide formed by the accumulation of one-dimensional needle-like compounds. This was verified by cross-sectional electron microscopy (see Figure 2 (e~f) The lead iodide layer modified by protonated imidazole salt buried with lactic acid appears fluffy.
[0085] The following tests and characterizations were performed on the perovskite films prepared in step S6 of the above Examples 1 to 3 and Comparative Example 1:
[0086] Characterization 1: X-ray diffraction analysis was performed, and the test results are shown in Figures 4 and 5 :
[0087] The annealing process of the perovskite film prepared in Example 3 and Comparative Example 1 was subjected to a quasi-in-situ X-ray diffraction test. The test results are as follows: Figure 4 As shown in the figure, during the annealing process, the perovskite wet film without the modification of protonated imidazolate salt buried with lactic acid has a high-intensity perovskite δ phase peak at the beginning of annealing due to the dense lead iodide layer, undesirable organic amine salt deposition and irresistible water damage. As time goes by, the δ phase will decompose lead iodide under heating conditions, so that the final perovskite film has excessive lead iodide, which is not conducive to the crystallization quality of the perovskite film; on the contrary, the perovskite wet film modified by protonated imidazolate salt buried with lactic acid forms a low-dimensional complex intermediate phase during the annealing process, weakening the formation of the δ phase, which strongly proves the effective reaction of the organic mixed solution and lead iodide, and as the annealing time increases, the peak intensity of lead iodide does not increase, indicating that the lead iodide reacts more, and the crystallization quality of the perovskite film with needle-shaped fluffy lead iodide composite nucleation interface as the crystallization framework is improved.
[0088] X-ray diffraction analysis was performed on the perovskite films prepared in Example 3 and Comparative Example 1. The test results are as follows: Figure 5 As shown in the figure, it can be seen that the main peak (100) at 14.1° of the perovskite film with the needle-shaped fluffy lead iodide composite nucleation interface as the crystal framework is significantly enhanced, and the lead iodide marker peak at 12.7° is suppressed, proving that the crystal quality of the product is improved.
[0089] Characterization 2, photoluminescence spectrum analysis, the test results are shown in Figure 6 :
[0090] The perovskite films prepared in Examples 1 to 3 and Comparative Example 1 were subjected to photoluminescence spectroscopy analysis. The conductive glass substrate and the SnO2 electron transport layer were peeled off before the test. The test results are shown in FIG. Figure 6 As shown. Figure 6 It can be seen that under the same excitation intensity, the buried interface modified by lactic acid protonated imidazolate salt shows a higher PL emission intensity, especially when the concentration of lactic acid protonated imidazolate salt solution is 0.60 mg / mL, the PL emission intensity is the strongest. This experiment shows that when the concentration of lactic acid protonated imidazolate salt solution is 0.60 mg / mL, the buried bottom modified perovskite film with needle-shaped fluffy lead iodide composite nucleation interface as the crystal framework has better inhibition of non-radiative recombination. Therefore, the 0.60 mg / mL lactic acid protonated imidazolate salt solution used in Example 3 is the optimal concentration.
[0091] Characterization 3: Field emission scanning electron microscopy and atomic force microscopy analysis, the test results are shown in Figure 7-8 :
[0092] The field emission scanning test results are as follows Figure 7 As shown in the figure, after the modification of protonated imidazolium salt buried by lactic acid, the grains in the perovskite film with needle-shaped fluffy lead iodide composite nucleation interface as the crystallization framework showed a significant increase in size, while the number of grain boundaries decreased. It can be inferred that the organic mixed solution can achieve good diffusion in the lead iodide composite nucleation interface and fully react and crystallize, effectively improving the crystallinity of the film. In addition, Figure 8 The atomic force microscopy analysis results shown further confirm that good crystallization conditions have an improving effect on the surface flatness of the perovskite film.
[0093] Test 1, high humidity stability test, test results see Fig. 9 , where the left picture is a field emission scanning electron microscope photo, and the right picture is an X-ray diffraction pattern;
[0094] In order to test the high humidity stability of the perovskite film prepared in Example 3 with the needle-shaped fluffy lead iodide composite nucleation interface as the crystal framework, the perovskite films prepared in Example 3 and Comparative Example 1 were stored in a 70±10% humidity environment for 600 hours, and the degradation of the perovskite crystals was analyzed by field emission scanning electron microscopy and X-ray diffraction. The results are as follows: Figure 7 As shown. Fig. 9 The field emission scanning electron microscope photo shown on the left also shows that the aged perovskite film with needle-shaped fluffy lead iodide composite nucleation interface as the crystal framework can still maintain its original structure; Fig. 9 The X-ray diffraction pattern shown on the right also shows that the (100) main peak at 14.1° representing the black phase perovskite (α phase) maintains high intensity, and the yellow phase perovskite (δ phase) at 11.7° decomposed under high humidity conditions is suppressed, indicating that under conditions of 70±10% humidity, the perovskite film with needle-shaped fluffy lead iodide composite nucleation interface as the crystallization framework can still maintain its physical and chemical properties and is not easily changed by the influence of high humidity environment.
[0095] Test 2, high temperature stability test, test results see Fig.10 , where the left picture is a field emission scanning electron microscope photo, and the right picture is an X-ray diffraction pattern;
[0096] In order to test the high temperature stability of the perovskite film prepared in Example 3 with the needle-shaped fluffy lead iodide composite nucleation interface as the crystal framework, the perovskite films prepared in Example 3 and Comparative Example 1 were placed in a high temperature environment of 85°C and heated for 900 hours, and the degradation of the perovskite crystals was analyzed by field emission scanning electron microscopy and X-ray diffraction. The results are as follows: Figure 8 As shown. Fig.10 From the field emission scanning electron microscope photo (left), it can be observed that only a small amount of perovskite film grains grown with the needle-shaped fluffy lead iodide composite nucleation interface as the crystal framework are destroyed, and the amount of lead iodide precipitation is small. Fig.10 (right) The X-ray diffraction pattern shows that the main peak at 14.1° shows high intensity, while the precipitation of lead iodide due to heat at 12.7° is not obvious. The above phenomenon shows that under high temperature conditions, the perovskite film with needle-shaped fluffy lead iodide composite nucleation interface as the crystal framework can still maintain its physical and chemical properties. This means that the light-absorbing layer has good stability in high temperature environments and is not easily changed by high temperature.
[0097] Example 4
[0098] This embodiment provides a perovskite solar cell. A perovskite film is prepared according to the preparation method of Example 3 in an environment with a humidity of 40±10%, and the prepared perovskite film light absorption layer is assembled on the perovskite solar cell.
[0099] Comparative Example 4
[0100] This comparative example provides a perovskite solar cell. A perovskite film is prepared according to the preparation method of comparative example 1 in an environment with a humidity of 40±10%, and the prepared perovskite film light absorption layer is assembled on the perovskite solar cell.
[0101] Comparative Example 5
[0102] This comparative example provides a perovskite solar cell, which is different from Example 4 in that the process of preparing the needle-shaped fluffy lead iodide composite nucleation interface in step S5 of Example 3 is carried out in a N2 gas glove box, and the process of preparing the perovskite film with the needle-shaped fluffy lead iodide composite nucleation interface as the crystallization framework in step S6 is carried out in an environment with strictly controlled humidity of 30-40%.
[0103] Comparative Example 6
[0104] This comparative example provides a perovskite solar cell, which is different from comparative example 4 in that the process of forming a nucleation interface of lead iodide in step S5 of comparative example 1 is carried out in a N2 gas glove box, and the process of preparing a perovskite film in step S6 of comparative example 1 is carried out in an environment with a strictly controlled humidity of 30-40%.
[0105] Test 3, photoelectric conversion efficiency test:
[0106] The perovskite solar cells prepared in Example 4 and Comparative Examples 4 to 6 were tested for photoelectric conversion efficiency. Forward scanning (FS, voltage from 0 V to 1.2 V) and reverse scanning (RS, voltage from 1.2 V to 0 V) were performed during the test. The test results are shown in Tables 1 and Fig.11 The left picture shows the photoelectric efficiency test of perovskite solar cells prepared in air, and the right picture shows the photoelectric efficiency test of perovskite solar cells prepared in a N2 atmosphere glove box.
[0107] The test results of Example 4 and Comparative Examples 4 to 6 are analyzed. From Table 1 and Fig.11 It can be seen that under the condition of a standard light intensity of 100 mW / cm², the photoelectric conversion efficiency of the perovskite solar cell provided in Comparative Example 4 is 22.98%, and the photoelectric conversion efficiency of the perovskite solar cell obtained by preparing a perovskite solar film and assembling it in the air in Example 4 is 24.25%. In Example 4, a perovskite film prepared by using a lactic acid protonated imidazole salt to modify an electron transport layer as a nucleation template to induce the growth of a needle-shaped three-dimensional fluffy lead iodide nucleation interface is applied to a perovskite solar cell, and its photoelectric conversion efficiency is significantly increased from 22.98% to 24.25%, effectively improving the photoelectric conversion efficiency of the perovskite solar cell. Compared with the optimal photoelectric conversion efficiency of 25.66% achieved by the perovskite solar cell prepared in the N2 glove box in Comparative Example 5, the gap between the two is small. This result strongly confirms that this scheme not only effectively improves the photoelectric performance of perovskite solar cells, but also has positive significance in broadening its preparation methods, and provides new ideas and methods for the industrial production and practical application of perovskite solar cells.
[0108] Table 1. Test results of photoelectric efficiency of perovskite solar cells prepared in air in Example 4 and Comparative Example 4
[0109]
[0110] The above are only preferred embodiments of the present application and are not intended to limit the present invention. Although the present application has been described in detail with reference to the examples, those skilled in the art can still modify the technical solutions recorded in the aforementioned examples or make equivalent substitutions for some of the technical features therein. However, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A perovskite film with a needle-shaped fluffy lead iodide composite nucleation interface as a crystal framework, characterized in that: It is prepared by dynamically spin-coating an organic mixed solution on the needle-shaped fluffy lead iodide composite nucleation interface and then annealing. The organic mixed solution is prepared by uniformly mixing formamidine iodide, methylammonium chloride and a second organic solvent; The method for preparing the needle-shaped fluffy lead iodide composite nucleation interface comprises the following steps: Step S1, preparing a lactic acid protonated imidazole salt solution: mixing lactic acid, 1-aminoethyl-3-methylimidazolium tetrafluoroborate, and water, stirring evenly to obtain a lactic acid protonated imidazole salt solution, wherein the molar ratio of lactic acid to 1-aminoethyl-3-methylimidazolium tetrafluoroborate is 1:1; and the concentration of the lactic acid protonated imidazole salt solution is 0.30-0.90 mg / mL; Step S2, preparing a lactic acid protonated imidazolate interface modification layer: dripping a lactic acid protonated imidazolate solution on the surface of the SnO2 electron transport layer, obtaining a wet film containing lactic acid protonated imidazolate by spin coating, and annealing the wet film containing lactic acid protonated imidazolate to obtain a lactic acid protonated imidazolate interface modification layer; Step S3, preparing a needle-shaped fluffy lead iodide composite nucleation interface: adding a lead iodide solution dropwise onto the surface of the lactic acid protonated imidazolium salt interface modification layer, obtaining a wet film containing lead iodide by spin coating, and annealing the wet film containing lead iodide to obtain a needle-shaped fluffy lead iodide composite nucleation interface.
2. The perovskite film with a needle-shaped fluffy lead iodide composite nucleation interface as a crystal framework according to claim 1, characterized in that: In the step S2, the annealing temperature is 80-120° C., and the annealing time is 5-10 minutes.
3. The perovskite film with a needle-shaped fluffy lead iodide composite nucleation interface as a crystal framework according to claim 1, characterized in that: In step S3, the lead iodide solution is prepared by mixing lead iodide and an organic solvent.
4. The perovskite film with a needle-shaped fluffy lead iodide composite nucleation interface as a crystal framework according to claim 3, characterized in that: The organic solvent is one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.
5. The perovskite film with a needle-shaped fluffy lead iodide composite nucleation interface as a crystal framework according to claim 4, characterized in that: The organic solvent is composed of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 9:
1.
6. The perovskite film with a needle-shaped fluffy lead iodide composite nucleation interface as a crystal framework according to claim 2, characterized in that: In step S3, the annealing temperature is 60-80° C., and the annealing time is 0.5-2 minutes.
7. A perovskite solar cell, characterized in that: It comprises a conductive glass substrate, a SnO2 electron transport layer, a perovskite film with a needle-shaped fluffy lead iodide composite nucleation interface as a crystal framework as described in any one of claims 1 to 6, a hole transport layer and a metal electrode layer which are arranged in sequence.
Citation Information
Patent Citations
Perovskite solar cell and preparation method thereof
CN113224241A
Perovskite solar cell based on lead iodide precursor engineering and preparation method thereof
CN116761443A